Addiction Recovery as Transformative Learning: Identity Change in Men Who Participated in Residential Treatment - Jordan, Daniel J.; Bedi, Robinder P. (Canadian Journal of Counselling and Psychotherapy, 2022)
Addiction causes much human suffering and exacts significant social and economic costs. Despite a plethora of theories related to addiction, these harms have not decreased, which suggests that new understandings are needed to make further progress. The purpose of this study was to provide an initial, early-stage evaluation of Addiction Recovery as Transformative Learning, a new model of addiction recovery that draws heavily on education literature, specifically on theorizing and research related to transformative learning. This study examined the narratives of addiction and recovery of seven male clients who had attended residential addiction treatment. Deductive content analysis was employed to see if participant accounts of their recovery experiences were consistent with the assertions of the model and could be captured adequately within its main constructs. Participant accounts strongly supported the aspects of the model tested by the study. Study results have important implications for addiction recovery and counselling, particularly within residential treatment settings.